Morphological Awareness: Reading and Writing in the Primary School (Revista de Estudos da Linguagem, 2024)
The main objective of the study is to analyze the relation between morphological awareness reading (fluency), writing and reading comprehension, in children with typical development(TD) and children with Specific Learning Disorder(SLD). The sample consists of 150 children european portuguese speakers(120 with TD and 30 children with SLD, the 2nd and 4th. Data collection included Grelha de Avaliação da Linguagem- Nível Escolar, Morphological Awareness Assessment Battery, Bateria de Avaliação da Leitura em Português Europeu, a writing test adapted and Teste de Idade de Leitura. In the statistical analysis of the results, the Mann-Whitney U Test was used to identify significant differences between the two groups of children. Furthermore, the Spearman’s test was used to study the correlation between morphological awareness with reading and writing, and with reading comprehension. There was a significant difference in the results of morphological awareness between groups and in both years. There was a significant correlation with greater impact between the performance of TD children on morphological awareness tests with reading and writing. There was also a significant correlation between morphological awareness and reading comprehension, having greater impact in children with SLD, in the 2nd and 4th. The morphological awareness can facilitate the learning of reading and writing, in both children with TD and SLD. Therefore, it will be important to explicitly teach morphological rules, in order to use the meanings conveyed by different morphemes and how morphemes are related, allowing children to use this knowledge as a strategy for reading and writing.